Perencanaan Pembangunan Gapura Tempat Wisata di Desa Lamaninggara Kec. Siompu Barat Kab. Buton Selatan - Muhammad Abdu; Muhammad Chaiddir Hajia; La Farji; Amsyal Amsyal (IAIN AMBON, 2022)
Lamaninggara Village is located in Siompu Barat District, South Buton Regency, Southeast Sulawesi Province. The construction site for the gate is located at the north entrance. It is hoped that the construction of the hamlet gate monument can add to the attractiveness and beautify the hamlet atmosphere. Currently, there is no gate for the Latamburu bathing tourist area which is a sign of a tourist area so that residents both from inside and outside the village can find out. so that the Lamaninggara Village Government wants the construction of the gate to make it look more attractive and beautify the atmosphere of the tourist attractions in accordance with the current development of building design. Therefore, before carrying out the structural design work, a meeting with the Lamaninggara Village Government was held and a survey in the village environment was carried out to find out an initial picture of the planned building. The gate building of Gawar hamlet, Pandowoharjo, Sleman is planned to have a height of 4.3 meters using a pair foundation using a reinforcement structure, the main structure using reinforcement, and the top of the iron plate. This community service activity can be continued by providing technical assistance during the construction of the monument later. Keywords: Lamaninggara Village, Gate, Tourism